2023
DOI: 10.1186/s10194-023-01629-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of high-voltage pulsed radiofrequency to treat patients with primary trigeminal neuralgia: a multicenter, randomized, double-blind, controlled study

Abstract: Background Trigeminal neuralgia (TN) is a debilitating pain disorder that still lacks an ideal treatment option. Pulsed radiofrequency (PRF), especially with high output voltage, is a novel and minimally invasive technique. PRF is regarded a promising treatment option for TN patients who respond poorly to medical treatment; however, the available evidence still lacks high quality randomized controlled trials (RCTs). Our study aimed to evaluate the long-term (1 year and 2 years) effects and safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Although the application of HVPRF on DRG have received increasing attention, studies have shown that HVPRF is more effective than SVPRF. Luo et al 7 demonstrated that a higher output voltage and current field intensity increased the analgesic effect for trigeminal neuralgia. Several clinical studies have also shown that increasing the output voltage of PRF can significantly improve refractory neuralgia of the infraorbital nerve 24 , and postherpetic neuralgia 25 without increasing the risk of side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the application of HVPRF on DRG have received increasing attention, studies have shown that HVPRF is more effective than SVPRF. Luo et al 7 demonstrated that a higher output voltage and current field intensity increased the analgesic effect for trigeminal neuralgia. Several clinical studies have also shown that increasing the output voltage of PRF can significantly improve refractory neuralgia of the infraorbital nerve 24 , and postherpetic neuralgia 25 without increasing the risk of side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Pulsed radiofrequency (PRF) is a minimally invasive technology proposed by Sluijter 2 , 4 and has been widely used to manage several types of refractory chronic pain, such as postherpetic neuralgia 5 , cervicogenic headache 6 and trigeminal neuralgia 7 . This technique works by delivering electrical fields and thermal pulses through the catheter tip to the target nerve or tissue without damaging these structures, and the clinical standard PRF parameters are as follows: the output voltage is 45 V, the current action time is 20 ms, the intermittent period is 480 ms, the oscillating frequency of the alternating current is 500 kHz and the maximum temperature of the electrode does not exceed 42 °C 8 .…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the above complications, we used PRFT in our clinical case. 22 PRFT was introduced by Sluijter in 1998. Since that time, PRFT has been widely used for various types of pain.…”
Section: Discussionmentioning
confidence: 99%
“…PRF has emerged as a promising alternative to RFT. PRF is a minimally invasive procedure that offers significant advantages, primarily its non-destructive nature, which helps avoid complications commonly associated with conventional RFT [ 16 , 17 ]. PRF has a distinct and beneficial mechanism of action.…”
Section: Discussionmentioning
confidence: 99%